1999
DOI: 10.1161/01.cir.99.19.2577
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Microparticles Promote Platelet Interaction With Subendothelial Matrix in a Glycoprotein IIb/IIIa–Dependent Mechanism

Abstract: Platelet microparticles bind to subendothelial matrix in vitro and in vivo and can act as a substrate for further platelet binding. This interaction may play a significant role in platelet adhesion to the site of endothelial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 39 publications
4
95
0
2
Order By: Relevance
“…After a 60-minute incubation, the bound protein was quantified by peroxidase-labeled monoclonal anti-biotin antibody, with O-phenylenediamine as a substrate, and optical density was measured in an ELISA reader (MR 5000, Dynatech), as previously described. 11 Nonspecific binding of biotin-labeled MCSP, determined in the presence of a 80-fold molar excess of unlabeled MCSP, was subtracted from total binding to obtain specific binding. Nonspecific binding was 11% of total binding.…”
Section: Characterization Of Recombinant Malaria Circumsporozoite Promentioning
confidence: 99%
See 1 more Smart Citation
“…After a 60-minute incubation, the bound protein was quantified by peroxidase-labeled monoclonal anti-biotin antibody, with O-phenylenediamine as a substrate, and optical density was measured in an ELISA reader (MR 5000, Dynatech), as previously described. 11 Nonspecific binding of biotin-labeled MCSP, determined in the presence of a 80-fold molar excess of unlabeled MCSP, was subtracted from total binding to obtain specific binding. Nonspecific binding was 11% of total binding.…”
Section: Characterization Of Recombinant Malaria Circumsporozoite Promentioning
confidence: 99%
“…11 Wells of 96-well microtiter plates were coated with glycolipids or soluble recombinant human P-selectin and blocked as described above. Platelets (1.25ϫ10 6 to 5ϫ10 6 /well) were added in HEPES-buffered saline containing 1% BSA and 1 mmol/L CaCl 2 .…”
Section: Platelet Adhesion Assaysmentioning
confidence: 99%
“…29 No specific staining was detected in early or late lesions, indicating that platelet deposition and granule release are unlikely to account for the observed accumulation of LTBP1.…”
Section: Ltbp1 Localization In Coronary Atherosclerosismentioning
confidence: 95%
“…During our initial review of the literature, we found a range of centrifugation conditions used to pellet microparticles: 10,000 Â g for 10 minutes [2], 14,000 Â g for 2 minutes [3], through 100,000 Â g for 1 hour [4,5]. Unable to find a consensus, we chose to use 13,000 Â g for 2 minutes to sediment microparticles for two reasons.…”
Section: Dear Editormentioning
confidence: 99%